Reinventing with the 3 Cs - Abd Razak, Dzulkifli (2007)
IN Shanghai last week, a group of academic, business and government leaders from 13 countries in the AsiaPacific region were invited to deliberate on the future of education. The inaugural regional summit to Reinvent Education for the 21st Century was supported by the Ministry of Education of China and held under the initiative of IBM's corporate community relations. Among them was Rosabeth Moss Kanter, a wellknown author and professor of business administration at Harvard University. In her keynote address, she expounded the principles of the 3Cs concept, competence and connections—in reinventing education.